COMPUTATION OF THE ENERGY CONSUMPTION FOR WARMING UP OF FLAT OAK DETAILS BEFORE THEIR BENDING (Innovation in Woodworking Industry and Engineering design, 2026)
A software program has been prepared in the calculation environment of Visual Fortran for solving of own 1D non-linear model of the one sided heating process of flat wood details. With the help of the program, the 1D non-stationary temperature field in flat oak details with initial temperature of 20 oC, moisture content of 0.15 kg.kg-1, thickness of 12 mm, 16 mm, and 20 mm during their 30 min one sided heating at temperature of 80 oC of the heating metal body has been calculated. After integration of the temperature field, the energy consumption for warming up of the details before their bending in the production of curved back parts of chairs has been calculated. The obtained results are graphically presented and analyzed.